Relazioni familiari e migrazioni tra diritto, religioni e culture (Stato, Chiese e pluralismo confessionale, 2024)
Family relationships and migrations between law, religions and cultureABSTRACT: In recent years, the social and multi-religious evolution of the family has contributed to redefined its morphology, varying its traits through a continuous work of cultural, ethnic and religious relocation. It frequently clashes with resistance typical of an institution that is in some ways still linked to traditional legal paradigms. It is consequently increasingly necessary to acquire technical tools that allow people to govern family relationships in the current “multicolor” context. The essay investigates the possibility of leaving ample space for private autonomy in the regulation of family relationships in the belief that in this way families are provided with flexible tools that conform to their own cultural and religious identity.SOMMARIO: 1. Dalla famiglia alle famiglie - 2. Le relazioni familiari multicolor - 3. La famiglia e i modelli cultural-religiosi - 4. I diritti religiosi come “argine” alla derivazione di alcuni modelli di famiglia - 5. La famiglia: dal totale dirigismo all’autonomia parziale.